Evaluation of heritable determinants of blood and brain serotonin homeostasis using recombinant inbred mice. (31st October 2013) - Ye, R.; Carneiro, A. M. D.; Airey, D.; Sanders‐Bush, E.; Williams, R. W.; Lu, L.; Wang, J.; Zhang, B.; Blakely, R. D.
<x xml:space="preserve">Abstract</x> The biogenic amine serotonin (5‐HT, 5‐hydroxytryptamine) exerts powerful, modulatory control over multiple physiological functions in the brain and periphery, ranging from mood and appetite to vasoconstriction and gastrointestinal motility. In order to gain insight into shared and distinct molecular and phenotypic networks linked to variations in 5‐HT homeostasis, we capitalized on the stable genetic variation present in recombinant inbred mouse strains. This family of strains, all derived from crosses between C57BL/6J and DBA/2J (BXD) parents, represents a unique, community resource with approximately 40 years of assembled phenotype data that can be exploited to explore and test causal relationships in silico. We determined levels of 5‐HT and 5‐hydroxyindoleacetic acid from whole blood, midbrain and thalamus/hypothalamus (diencephalon) of 38 BXD lines and both sexes. All 5‐HT measures proved highly heritable in each region, although both gender and region significantly impacted between‐strain correlations. Our studies identified both expected and novel biochemical, anatomical and behavioral phenotypes linked to 5‐HT traits, as well as distinct quantitative trait loci. Analyses of these loci nominate a group of genes likely to contribute to gender‐ and region‐specific capacities for 5‐HT signaling. Analysis of midbrain mRNA variations across strains revealed overlapping gene expression networks linked to 5‐HT synthesis and metabolism. Altogether, our studies provide a rich profile of genomic, molecular and phenotypic networks that can be queried for novel relationships contributing risk for disorders linked to perturbed 5‐HT signaling.